Design optimization of a novel cryo-polygeneration demonstrator developed in Singapore – techno-economic feasibility study for a cooling dominated tropical climate - Tafone, Alessio (2023)
The global growth in demand for space cooling is becoming a pressing and critical energy issue potentially having a major impact on the electricity system and the environment. Due to their capabilities to efficiently provide multiple energy services (i.e. mainly electricity, cooling and heat) for urban districts like universities and hospitals, decentralized polygeneration systems can significantly contribute to tackle this issue with several energetic, economic and environmental benefits. Indeed, their impact on both energy efficiency and emissions reduction might be disruptive especially in urban districts located in a tropical region, where the cooling demand is approximately stationary throughout the whole year. Often overlooked by current studies, a systematic and generalized research with an on-site real application on the decarbonization in tropical climate by means of decentralized polygeneration systems is still lacking. This study investigated the techno-economic and environmental benefits of renewable energy sources, storage units and time-varying loads (electricity and cold) on the performance of a real project, i.e. a novel cryo-polygeneration system in a cooling dominated environment. Expected to be in operation in 2023 at the NTU campus located in Singapore, the system is designed to become the first showcase of systems integration that can be exported overseas as an urban solution for tropical climate. Diverse design scenarios and case studies (university and commercial buildings) were firstly dynamically modeled in TRNSYS environment and subsequently optimized in GenOpt software to determine the optimal size of critical components such as gas turbine, absorption chiller, vapour compression chiller, cold thermal energy storage and solar PV units with electrical energy storage as well as the impact of different load profiles on the techno-economic and environmental analysis. For both case studies the optimal design capacities derived confirms higher efficiency and economic performance than the reference system, i.e., a baseline case scenario where all the demands are supplied by the electricity in a grid connected environment. Indeed, the results show that the cryo-polygeneration systems including both renewables and cold thermal energy storage achieve more than 38% and 40 % total annualized cost savings and up to 19 % CO2 reduction, when compared to the baseline case scenario. The main outcomes are of great interest to academia and industry and contribute significantly to developing an efficient, cost-effective and environmentally friendly decentralized cryo-polygeneration system.